PENGARUH BIAYA PENDIDIKAN PERSONAL TERHADAP PRESTASI BELAJAR SISWA DI SMA NEGERI 5 PEKANBARU - M Arif; Syakdanur Nas; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims is determinate to find out the effect of personal education costs to learning achievement. This research is a quantitative descriptive study using simple linear regression analysis to examine the effect of personal education costs on student achievement in class X IPS and XI IPS in SMA Negeri 5 Pekanbaru. The sampling technique uses simple random sampling technique. The process of taking data by giving a questionnaire and documentation. Data analysis techniques used are Normality Test, Heteroscedasticity Test, and T-Test with SPSS. The results showed that there was a significant influence between personal education costs on student learning achievement and R2 contribution of 22.8% on student learning outcomes in Pekanbaru 5 State Senior High School. The results of this study indicate that the cost of personal education has a positive influence on student learning achievement, which means that students' personal education costs can improve their learning achievement. With this in mind to improve student learning achievement there is a need for sufficient personal costs so that the learning process is more effective.Keywords: Personal Education Cost, Learning Achievement.